Interleukin-10 Producing Regulatory B Cells Transformed CD4+CD25− Into Tregs and Enhanced Regulatory T Cells Function in Human Leprosy - Tarique, Mohd.; Naz, Huma; Kurra, Santosh V.; Saini, Chaman; Naqvi, Raza Ali; Rai, Reeta; Suhail, Mohd; Khanna, Neena; Rao, Donthamshetty N.; Sharma, Alpana (Frontiers in Immunology, 2018)
Regulatory B cells are known to exhibit their regulatory functions through Interleukin 10 (IL-10) cytokine which suppresses inflammation. There are only a few studies explaining the phenotype and functioning of these cells in contribution to host immunity in leprosy. Here, we evaluated the role of interleukin-10 producing regulatory B-cells (Bregs) in the pathogenesis of leprosy and assessed their immunoregulatory effects on Tregs and effector T cells. We found an increased frequency of Bregs and increased expression of their immune modulatory molecules (IL-10, FoxP3 and PDL-1) in leprosy patients. The potential immunoregulatory mechanism of Bregs was also investigated using MACS sorted Teff (CD4+CD25-) and Treg (CD4+CD25+) cells were co-cultured with Bregs to elucidate the effects of Bregs on effector T and regulatory T-cells. Cell co-culture results showed that purified Bregs cells from leprosy patients convert the CD4+CD25- cells into CD4+CD25+ cells. Cell co-culture experments also demonstrated that leprosy derived IL-10 producing Bregs enhance the FoxP3 and PD-1 expression in Tregs and enhanced Tregs activity. Blocking of IL-10 receptor confirmed that IL-10 producing Breg has immunomodulatory effect on Tregs and effector T cells as effector T cells and are not converted into Tregs and enhanced expression of FoxP3 and PD-1 was not observed on Tregs. Collectively, these findings demonstrate that IL-10-producing Breg cells play an important mechanism in controlling the immunopathogenesis of leprosy and have an immunomodulatory effect on Tregs and effector T cells. Our findings may pave way for novel targets of IL-10 producing Bregs for immunotherapy in leprosy patients.